A confused drug addict: the importance of considering sepsis. Issue 3 (May 1996) - Cornelius, P; Pourgourides, E; Meek, S
Abstract : The case is reported of a 35 year old heroin addict presenting with acute confusion which was later found to be due to meningococcal meningitis. Other than his altered mental state, the only abnormal finding on examination was a mild pyrexia.